1988
DOI: 10.1111/j.1365-2710.1988.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Drugs to End-Line Filters: A Study of Four Commonly Administered Drugs in Intensive Care Units

Abstract: The binding of diazepam, digoxin, dopamine and fentanyl to different 0.2 microns end-line filters was investigated under simulated infusion conditions. All the drugs were diluted in either 5% dextrose or 0.9% NaCl infusion fluid. For digoxin and diazepam a marked reduction in the amount of drug delivered to the patient in the first 20-60 min of infusion is observed. For dopamine, the drug loss was less pronounced and no fentanyl was absorbed to the filters during the infusion experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Some authors reported no losses on any type of digoxin filter, 11,12 while others reported losses as high as 73% when filtration was performed within the first 20 minutes using 0.22 µm filters. 13 Saturation of the filters might eventually limit losses. In the present study, the large quantity filtered could explain why no losses were observed when solutions were prepared using the copy of the commercial vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported no losses on any type of digoxin filter, 11,12 while others reported losses as high as 73% when filtration was performed within the first 20 minutes using 0.22 µm filters. 13 Saturation of the filters might eventually limit losses. In the present study, the large quantity filtered could explain why no losses were observed when solutions were prepared using the copy of the commercial vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Hirakawa and colleagues 95 found that in-line filters decrease concentration of amphotericin B in filtered fluid, the proportion being dependent on the type of filter material used. Other authors have also reported a decrease in the availability of drugs such as digoxin and diazepam when infused through in-line filters 96 .…”
Section: Complications With In-line Filtersmentioning
confidence: 98%
“…De Muynck et al [32 ]reported the binding of different drugs to four different in-line filters during simulated infusion. These authors found filter absorption for digoxin and diazepam, little absorption for dopamine, while no absorption was detected for fentanyl.…”
Section: Discussionmentioning
confidence: 99%